RELATIONSHIP BETWEEN KNOWLEDGE LEVEL AND DENGUE PREVENTIONBEHAVIOR IN TELAGAJAYA VILLAGE COMMUNITY, PAKISJAYA SUBDISTRICT, KARAWANG REGENCY IN 2023 - Sholeha; Arabta M. Peraten Pelawi; Baltasar S. S. Dedu (Rena Cipta Mandiri, 2023)
Dengue fever is a disease accompanied by bleeding and sometimes shock that can cause death of sufferers, especially in community sufferers. Knowledge is closely related to behavior, where the better one's level of knowledge the better one's behavior. Research Objective: This study aims to determine the relationship between the level of knowledge and dengue prevention behavior in the community. Research Method: This study is quantitative analytical observational with cross-sectional approach and purposive sampling technique and uses direct and online questionnaires via google form to 106 respondents in RT 02 / RW 01. Researchers use the chi square statistical test to determine the relationship between the two variables. Research Results: Based on the results of Chi square test analysis with the results of respondents who have high knowledge as many as 91 (85.8%) and respondents with sufficient behavior towards dengue prevention as many as 74 respondents (69.8%) obtained p-value (0.000) so that it is stated that H0 is rejected Ha is accepted. Conclusion: There is a relationship between the level of knowledge and dengue prevention behavior in RT 02 RW 01 Telagajaya Village